The circles of life (8) About this issue [colophon] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
This Millennium supplement to Spore was compiled by Paul Osborn with contributions from O Neil Cuffe, Zazah Razafindrazaka, Huguette Samgot and A Soares de Melo and was designed by Bernard Favre, Denis Delebecque and Pascale Thiers.Publisher:...